Para un examen crítico del comparatismo francés - Riaudel, Michel (Universidad Nacional del Litoral, 2019)
Brazilian literature is notoriously absent from the syllabi contents of exams for Modern Languages teachers aspiring to find employment. This clearly indicates a reduction in the scope of the discipline, thus favouring the traditional Franco–Anglo–German spectrum. We gather that it is necessaryto embrace a worldwide perspective and establish a threshold that should more proportionally represent foreign literatures. This clearly implies a consideration of what constitutes literary value and also shows a certain degree of bias in studies carried out under a strict national frame of mind. Thus, including Brazilian texts —as well as other ignored writings— in Comparative Literature Studies would help to bring the national pedestal of literature to a more accurate perspective.